Phenotypic, genetic and environmental trends for first lactation traits of Sahiwal cattle - Raja, K.N,; H.K.Narula,; B.K.Joshi, (Journal of Livestock Biodiversity, 2025)
Various methods have been developed to measure the genetic change in breeding stocks under selection. However, problem remains in accumulated data or in populations where no control comparisons are available. Phenotypic trend is the change in yearly mean phenotypic effect over the years, which includes the genetic and environmental components. This partitioning would reflect the effectiveness of selection programme undertaken over the years and will be helpful in suggesting corrective measures for further improvement of various economic traits. Production performance for a period of twenty-four years (1980-2004) of 272 Sahiwal cattle maintained at NDRI, Karnal were analyzed for the genetic change which revealed negative phenotypic trend for first lactation milk yield, 305 days milk yield, lactation length, lactation milk yield per day of lactation length and lactation milk yield per day of calving interval, while the genetic trends were positive for most of the traits. Based on the standard errors, the different methods were compared and it is concluded that method - IV (Powell and Freeman) is the most precise method for estimation of genetic trends for economic traits.